Training on Determining Beyond Use Date (BUD) on Pharmacy Practice at Surabaya Health Vocational School - Wibowo, Teguh Setiawan; Negara, Sri Bintang Sahara Mahaputra Kusuma (Jurnal Pengabdian Masyarakat Formosa, 2024)
All drugs must be injected immediately after being prepared because the life of the drug can be shorter and it no longer refers to the Expiration Date (ED). If the medicine is not injected immediately, then to maintain the quality of the medicine before the BUD limit is to give the medicine vial a mark of the date and time the medicine was prepared and it must be stored according to storage requirements. The method used theoretical presentation, question/answer, discussion and practice offline in one of Surabaya Health Vocational School classrooms. The results are the community service activities through training on determining the Beyond Use Date (BUD) in Pharmacy practice at the Surabaya Health Vocational School received a positive response and the participants were very enthusiastic. It is hoped that there will be special standards established by the Surabaya Health Vocational School to help provide understanding regarding determining the Beyond Use Date (BUD) in the pharmaceutical practice and further collaboration with the Health Service, Community Health Center or Hospital on an ongoing basis.